Does Metastatic Lymph Node SUVmax Predict Survival in Patients with Esophageal Cancer? - Vatankulu, Betül (Mol Imaging Radionucl Ther, 2015)
OBJECTIVE: We aimed to investigate the SUVmax of primary tumor and metastatic lymph node in predicting survival in patients with esophageal cancer. METHODS: We retrospectively analyzed patients with esophageal cancer between 2009 and 2011 who had FDG positron-emission tomography (PET)/computed tomography (CT). All patients were followed-up to 2013. Clinical staging, SUVmax of primary tumor and metastatic lymph node were evaluated. RESULTS: One hundred seven patients were included in the study. All patients were followed-up between 2 and 49 months. The mean SUVmax of primary tumor and metastatic lymph node were 19.3±8.8 and 10.4±9.1, respectively. Metastatic lymph node SUVmax had an effect in predicting survival whereas primary tumor SUVmax did not have an effect (p=0.014 and p=0.262, respectively). Multivariate Cox regression analysis showed that clinical stage of the disease was the only independent factor predicting survival (p=0.001). CONCLUSION: Among patients with esophageal cancer, the value of primary tumor SUVmax did not have an effect on survival. Clinical stage assessed with FDG PET/CT imaging was found to predict survival in esophageal carcinoma. Additionally, lymph node SUVmax was identified as a new parameter in predicting survival in the present study.